Digital towns : accelerating and measuring the digital transformation of rural societies and economies /: accelerating and measuring the digital transformation of rural societies and economies. (2022) - Lynn, Theo; Rosati, Pierangelo; Conway, Edel; Curran, Declan; Fox, Grace; O'Gorman, Colm
No abstract available